2004
DOI: 10.2134/jeq2004.0844
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Volatilization from Marsh–Pond–Marsh Constructed Wetlands Treating Swine Wastewater

Abstract: Ammonia (NH3) volatilization is an undesirable mechanism for the removal of nitrogen (N) from wastewater treatment wetlands. To minimize the potential for NH3 volatilization, it is important to determine how wetland design affects NH3 volatilization. The objective of this research was to determine how the presence of a pond section affects NH3 volatilization from constructed wetlands treating wastewater from a confined swine operation. Wastewater was added at different N loads to six constructed wetlands of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 8 publications
(11 reference statements)
5
34
0
Order By: Relevance
“…These wetlands had sloped bottoms, and denitrification was higher at the upper slope area where oxygen was more available to facilitate nitrification of the ammonia in the wastewater. These apparent high losses via denitrification are in agreement with the recently reported very high N removal by constructed wetlands in Ontario, Canada (Kadlec and Bishay, 2005).At the higher N loading rates, gaseous losses were also the major N removal pathway for N on MPM wetlands (Poach et al, 2003(Poach et al, , 2004a. Whereas Poach et al (2003) measured the volatilization of ammonia at various N loading rates, it was also important to assess denitrification at these varying loading rates.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…These wetlands had sloped bottoms, and denitrification was higher at the upper slope area where oxygen was more available to facilitate nitrification of the ammonia in the wastewater. These apparent high losses via denitrification are in agreement with the recently reported very high N removal by constructed wetlands in Ontario, Canada (Kadlec and Bishay, 2005).At the higher N loading rates, gaseous losses were also the major N removal pathway for N on MPM wetlands (Poach et al, 2003(Poach et al, , 2004a. Whereas Poach et al (2003) measured the volatilization of ammonia at various N loading rates, it was also important to assess denitrification at these varying loading rates.…”
supporting
confidence: 82%
“…The wetlands were constructed at the swine facility of the North Carolina A & T State University farm in Greensboro, NC, in 1995 and consisted of six sets of MPM wetland cells (Poach et al, 2004a(Poach et al, , 2004b …”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 3, the results of diluted and non-diluted wastewater showed that there is no significant inhibition effect when using original swine wastewater. Compared with the compositions reported in the literature, the swine wastewater collected from the uncovered lagoon has a lower COD value of 2050-2600 mg/L [27] and a lower ammonia content (<180 mg/L) [28], representing a low-strength wastewater that might be used directly as the algal medium. In addition, algal biomass yield in diluted wastewater is similar to that of proteose medium, which might be limited by the nutrients available.…”
Section: Effect Of Co 2 and Dilution On Biomass Yieldsmentioning
confidence: 75%
“…51 % total N and 26% total P from swine wastewater (Poach et al, 2004). Constructed wetlands can also release N as NH 3 • although this has been shown to be a relatively small portion of total N loss (Poach et al .. 2002). The main limiting factor for denitrification in these systems is the conversion of N to nitrate (Hunt et al.…”
Section: Slurry and Liquid Manure Systemsmentioning
confidence: 99%